THE MAIN APPROACHES TO STUDYING THE GENDER CATEGORY FROM SCIENTIFIC - Shakirova, Saida (Журнал иностранных языков и лингвистики, 2023)
Our article Gender Category Separated from Specific Grammatical Functions in Modern English looks at several categories of cultural history.